Complexo probiótico BAC-TRAT® na água e em dietas para tilápia-do-Nilo - Fonseca, José Rafael Soares (2019)
The aim of this work was to evaluate the effects of the probiotic in two ways of application (feeding and water), on zootechnical performance, hematological, intestinal and hepatic alterations of Nile tilapia (Oreochromis niloticus), maintained at low temperature conditions. Were used 108 juveniles with an initial mean weight of 8.41 ± 0.7 g and 8.09 ± 0.5 cm of total length, randomly distributed in 18 tanks with 18 L capacity and six fishes in each experimental unit for40 days in different groups: control treatment (T0), without receiving probiotic; addition of probiotic in water (T1) and probiotic diet (T2). For the analyzes of zootechnical performance of tilapia, there was no significant variation (p> 0.05). Regarding hematological parameters, there were significant leukocyte and lymphocyte effects (p<0,05) for the fish that received probiotics in the diet and those that not received, being observed a reduction in the values compared to the control and none effect was observed on the number of neutrophils and monocytes and on blood glucose after the experiment. For the centesimal composition of the carcass it was observed that the application of the probiotic in the water caused significant increases in the contents of ethereal extract, whereas the ash content was higher values in fish that received probiotic in water and in feed. The morphology of intestinal villi (height, width and ply of the tunic) and histomorphometry of hepatocyte nuclei (perimeter, area, volume and circularity) differed (p<0,05) between treatments and revealed effects associated with improvements in nutrient availability when the probiotic was applaied in both forms. It is concluded that the use of probiotic during low temperatures does not present beneficial effects to the growth of Nile tilapia, but it contributes to the increase of the villi area and influenced the area and the volume of the nucleus of the hepatocytes.